Análise das propriedades estruturais, morfológicas e mecânicas de duas marcas comerciais diferentes de dissilicato de lítio para o sistema CAD/CAM - Tavares, Lucas do Nascimento (2017)
The aim of the present study was to compare two different brands of lithium disilicate CAD/CAM blocks (IPS e.max CAD and Rosetta SM CAD/CAM), evaluated by structural, morphological and mechanical properties. Two specimens of each group were analyzed using x-ray diffraction (XRD) to evaluate the structures of the ceramic material. Morphologic properties were analyzed using the Scanning Electron Microscopy (SEM) before and after the heat treatment; and porosity test was performed using a 3D micro-computed tomography analyses (micro-CT). Ten specimens of each group were submitted to three-point flexure strength and microshear bond strength tests, to analyze the mechanical properties of both brands. Mean values of porosity test and three-axial flexural strength were analyzed by t Test, and the microshear bond strength was analyzed by Anova two-way. All tests used a significance level of α=0.05. The structure results performed by XDR, presented high peak positions corresponding to the standard lithium metasilicate and lithium disilicate, with similar intensities for both tested groups. The morphologic results demonstrated similar patterns of crystalline structure, before and after the heat treatment and the porosity test showed no difference between the number and size of the pores found. Both mechanical tests results did not present statistically significant differences between the samples. Based on the results, there was no difference in relation to their structural, morphological and mechanical properties, between the two commercial brands tested.